Pelvic Exenteration: An Updated Mini-Review from 1948 to 2020 - Unal, Ethem; Yıldız, Abdullah; Yuksekdag, Sema; Fırat, Aysun (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
Introduction. Pelvic exenteration (PE) is a curative or palliative radical surgical procedure applied for advanced or recurrent pelvic or perineal cancers. From 1948 to date, improvements in surgical techniques, including urinary conduits and pelvic reconstruction, have improved its morbidity and mortality. Aim. The present study reviews the evolution of PE, indications, complications and current results. Material and methods. Large case series and studies on PE were searched in PubMed, covering all years available, and recent applications of PE were reviewed. Results. Indications of PE are primary or locally advanced tumors (cervix. rectum. vulva. bladder), recurrence after radiotherapy (cervix), recurrence after primary resection (vulva, vagina, cervix, rectum) and palliative treatment for advanced tumors or pubic fistulas. Contraindication are distant metastases, involvement of iliac vessels, pelvic side-wall or para-aortic lymph nodes and invasion of sacrum proximal to S1/S2 or sciatic foramen. However, recent studies have reported more radical resections, including side-wall and vessels. Patient’s health condition and fitness are also important in decision-making. Conclusion. PE can be the last chance of cure or improving quality of life for advanced or locally recurrent pelvic cancers. 5-year survival rates with PE are better, but complications of such a radical surgery are still high, and should be improved.
Keywords: complications; indications; morbidity; mortality; pelvic exenteration